Entrepreneurship education – paradoxes in school–company interaction. Issue 7 (27th March 2020) - Sommarström, Kaarina; Oikkonen, Elena; Pihkala, Timo
Abstract : Purpose: The purpose of this paper studies the role of paradoxes in the adoption of entrepreneurship education (EE) in schools. Design/methodology/approach: Qualitative research methods were used, and the data were collected via semi-structured interviews with Finnish teachers and principals. Findings: Paradoxes are an important factor slowing the adoption of EE. Paradoxes appear to arise from teachers' misunderstandings, high personal standards of pedagogy and an unwillingness to change their routines. In schools, principals still regard EE as a newcomer that is easily abandoned should any difficulties emerge. The principals show unwillingness to take responsibility for managing EE or to establish relationships with companies. Research limitations/implications: The study represents Finnish practice in basic education. Due to the qualitative methodology applied, the generalizability of the results is limited. Quantitative research on the teachers' and principals' behaviour related to paradoxes in EE is needed. Furthermore, the pedagogical prioritization related to the introduction of EE warrants more research. Practical implications: The results suggest good opportunities exist in training to prepare teachers and principals to anticipate the difficulties of EE. Originality/value: The study introduces a new understanding of the difficulties in the adoption of EE. Paradoxes are important factors to take into account in the promotion of EE. Paradoxes stem from teachers' misunderstandings, misconceptions and their unwillingness to change. Principals seem unwilling to assume their responsibilities in managing EE. The study highlights opportunities for managing the emergence of these paradoxes by preparing teachers and principals better on the difficulties and unexpected outcomes of EE.